Search for resonances decaying to three W bosons in proton-proton collisions at sqrt[s]=13 TeV - Tumasyan,A; Adam,W; Andrejkovic,JW; Bergauer,T; Chatterjee,S; Dragicevic,M; Del,Valle AE; Frühwirth,R; Jeitler,M; Krammer,N; Lechner,L; Liko,D; et al. (Physical Review Letters, 2022)
A search for resonances decaying into a W boson and a radion, where the radion decays into two W bosons, is presented. The data analyzed correspond to an integrated luminosity of 138  fb^{-1} recorded in proton-proton collisions with the CMS detector at sqrt[s]=13  TeV. One isolated charged lepton is required, together with missing transverse momentum and one or two massive large-radius jets, containing the decay products of either two or one W bosons, respectively. No excess over the background estimation is observed. The results are combined with those from a complementary channel with an all-hadronic final state, described in an accompanying paper. Limits are set on parameters of an extended warped extra-dimensional model. These searches are the first of their kind at the LHC.